Modern treatment of supraventricular tachycardia - A. I. Tarzimanova; V. I. Podzolkov (Кардиоваскулярная терапия и профилактика)
Supraventricular tachycardia (SVT) is one of the most common arrhythmias. The prevalence of SVT varies widely in different countries and is 2,25 per 1,000 people in the general population. SVT reduce the quality of life of patients, and in some cases can worsen the prognosis. In patients with cardiovascular disease, the risk of SVT increases. Therapy of SVT is selected depending on the stability of hemodynamic and the QRS width. Until now, the treatment of SVT remains an urgent issue of modern cardiology, since despite the high effectiveness of catheter ablation, antiarrhythmic therapy plays an important role.